Drivers and barriers of sustainability-oriented innovations in Brazilian denim treatment facilities: an expert-driven decision support - Sueydy Cordeiro Gomes Brandão; Marcele Elisa Fontana; Wesley Douglas Oliveira Silva; Gilson Lima da Silva (Humanities & Social Sciences Communications)
Abstract The textile and apparel sector, particularly denim treatment facilities (DTFs), is responsible for significant environmental impacts, especially in water-scarce regions like Pernambuco, Brazil. This study explores the drivers and barriers to sustainability-oriented innovation (SOI) in small and medium-sized DTFs, aligning with the Sustainable Development Goals (SDGs), specifically SDG 9 (Industry, Innovation, and Infrastructure) and SDG 12 (Responsible Consumption and Production). Using a mixed-methods approach, the research initially conducted a systematic literature review to identify sixteen drivers and twenty-seven barriers. These were then evaluated through expert insights, synthesized using the Nominal Group Technique (NGT), and triangulated with interviews conducted with local DTF managers. The findings reveal that only two drivers, primarily regulatory compliance and managerial support, and fourteen barriers are relevant in the local context, underscoring the significant challenges companies face in adopting sustainable practices. The paper contributes to both theory and practice by offering a decision-making model to guide managers and policymakers in fostering SOI within regional contexts, despite the challenges posed by limited infrastructure and regulatory complexities. This research highlights the need for enhanced policy support, public awareness, and technological investment to facilitate SOI in similar industrial sectors.